2013
DOI: 10.1111/acem.12105
|View full text |Cite
|
Sign up to set email alerts
|

Marked Reduction in Length of Stay for Patients With Psychiatric Emergencies After Implementation of a Comanagement Model

Abstract: Objectives: Patients with psychiatric emergencies often spend excessive time in an emergency department (ED) due to limited inpatient psychiatric bed capacity. The objective was to compare traditional resident consultation with a new model (comanagement) to reduce length of stay (LOS) for patients with psychiatric emergencies. The costs of this model were compared to those of standard care.Methods: This was a before-and-after study conducted in the ED of an urban academic medical center without an inpatient ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…In other words, nurses are more sensitive to physical complaints than psychological ones. The results support previous findings that nurses do emphasize and focus on physical symptoms rather than psychological ones in emergency departments [6,10]. However, the question remains whether nurses lack the knowledge to manage or confused about the way to manage psychological distress while assessing physical ones.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, nurses are more sensitive to physical complaints than psychological ones. The results support previous findings that nurses do emphasize and focus on physical symptoms rather than psychological ones in emergency departments [6,10]. However, the question remains whether nurses lack the knowledge to manage or confused about the way to manage psychological distress while assessing physical ones.…”
Section: Discussionsupporting
confidence: 88%
“…Appropriate management of patients with psychological distress was found to improve quality of life, decrease recurrent visits for non-cardiac chest pain, and to lower depressive and anxiety symptoms [9]. Moreover, previous studies reported that management of psychological distress in EDs is associated with decreased workload, length of stay, and financial burden of health care services [9,10]. Such reports enhanced the reciprocal benefits of appropriate management of psychological distress between nurses and their patients at EDs.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies would address the concerns highlighted in this review regarding study quality as well as provide evidence of model generalisability and allow for assessment of model feasibility. In addition, the evaluation of different resource-based models—with a particular focus on varying multi-disciplinary components and the function of paediatric-trained mental health consultants vis-à-vis ED staff (ie, consultation–liaison services33 or telehealth/telemedicine services)34—would provide clinically translatable information that could enhance existing ED services in general and paediatric EDs, while comparative effectiveness studies of different specialised models of care could help ED administrators and clinicians select among models of potentially different effects.…”
Section: Discussionmentioning
confidence: 99%
“…p=.001) 30 . There was no relationship between the duration of cover of the psychiatry service and waiting times.…”
Section: Accepted Manuscriptmentioning
confidence: 94%